Characterization of Aerosols in an Underground Mine during a Longwall Move - Bugarski, Aleksandar D; Hummer, Jon A; Vanderslice, Shawn; Shahan, Michael R (Mining engineering, 2020)
A study was conducted in an underground mine with the objective to identify, characterize, and source apportion airborne aerosols at the setup face and recovery room during longwall move operations. The focus was on contributions of diesel- and battery-powered heavy-duty vehicles used to transfer equipment between the depleted and new longwall panels and diesel-powered light-duty vehicles used to transport personnel and materials to various locations within the mine. Aerosols at the setup face were found to be distributed among diesel combustion-generated submicrometer and mechanically generated coarse aerosols. According to the data, the submicrometer aerosols downstream of the setup face were sourced to diesel exhaust emitted by vehicles operated inside and outside of the panel. Depending on the intensity of the activities on the panel, the outby sources contributed between 12.5 and 99.6% to the average elemental carbon mass flow at the setup face and recovery room. Extensively used light-duty vehicles contributed measurably to the elemental carbon concentrations at the setup face. The number concentrations of aerosols downstream of the setup face were associated with aerosols generated by combustion in diesel engines operated in the shield haulage loop and/or outside of the longwall panels. Entrainment of road dust by diesel or battery-powered load-haul-dump vehicles operated near the measurement site appears to be the primary source of mass concentrations of aerosols. The findings of this study should help the underground mining industry in its efforts to reduce exposures of miners to diesel and coarse aerosols.